The Adsorption of Copper, Lead Metal Ions, and Methylene Blue Dye from Aqueous Solution by Pure and Treated Fennel Seeds - Ntandokazi Mabungela; Ntaote David Shooto; Fanyana Mtunzi; Eliazer Bobby Naidoo (Adsorption Science & Technology)
This research work reports on pure and acid-treated fennel seed biomaterials for the removal of metal ions of copper Cu(II), lead Pb(II), and methylene blue (MB) dye from aqueous solution by batch adsorption. Pure fennel seeds were labelled as PFS; nitric and sulphuric acid-treated seeds were designated as NAFS and SAFS, respectively. The adsorbents were characterised by SEM, EDX, FTIR, XRD, and BET. The SEM images revealed that the surface of the adsorbents was porous. However, physicochemical characterization further revealed that BET surface area, pore size, and pore width increased for NAFS and SAFS compared to PFS. FTIR results revealed that the peaks for cellulose −COC and −OH decreased considerably for NAFS and SAFS; this indicated that cellulose was hydrolyzed during acid treatment. Adsorption data showed that all biomaterials had a higher affinity for MB dye more than Pb(II) and Cu(II) metal ions. The maximum adsorption capacities onto PFS were 6.834, 4.179, and 2.902 mg/g and onto NAFS are 15.28, 14.44, and 4.475 mg/g, while those onto SAFS are 19.81, 18.79 and 6.707 mg/g respective for MB dye, Pb(II), and Cu(II) ions. Postadsorption analysis revealed that adsorption of Pb(II) and Cu(II) was controlled mainly by the electrostatic attraction, while that of MB was synergistic of electrostatic attraction, π-π interaction, and hydrogen bond. It was found that the uptake processes of MB dye onto all adsorbents fitted Freundlich while both cations were described by Langmuir model. The thermodynamic parameters ΔHo and ΔGo indicated the endothermic nature and spontaneity of the processes, respectively.